Laparoscopic pyeloplasty in neonates and infants is safe and efficient - Langreen, S.; Ludwikowski, B.; Dingemann, J.; Ure, B. M.; Hofmann, A. D.; Kuebler, J. F. (Frontiers in Pediatrics, 2024)
± 43 minutes) than for OP (109 ± 32minutes, p < 0.001). However, mean operating time was not longer in the patient group receiving LP at ≤ 6weeks (145 ± 21.6) compared to our main cohort receiving LP. Length of stay was not significantly different between the groups. Four patients after LP required emergency nephrostomy compared to one patient after OP. Rate of Revision-pyeloplasty in our main cohort aged 0-6 months at surgery was 8% in the patient group receiving LP and 14% in the patient group receiving OP (not significant) . Three revisions after LP were due to persistent UPJO, one due to stent migration. Only one patient requiring revision-pyeloplasty was less than 6 weeks old.To our knowledge this is one of the largest collectives of laparoscopic pyeloplasty performed in infants, while being the youngest cohort published to date. LP in neonates and infants under 6 months appears to be as effective as open surgery based on our experience.